" 1 " : ,(AND)* - (OR) + B : .

:+
x+0 = 0+ x = x

• • •
x *1 = 1* x = x

:*:
x+ y = y+x x* y = y*x

:
x *( y + z ) = x * y + x * z x + ( y * z ) = ( x + y ) *( x + z )

: x + x =1 x* x = 0 :
(a * b)* c = a *(b * c) (a + b) + c = a + (b + c) x*x = x

x+x = x

x=x

:
*, AND, &, ^ +, OR, ∨

¬x, NOT ( x), x, x '

:
x*x = x x *1 =

.1

x* x

=
neutral _ element

xx + 0

=
complement

xx + xx

=
distributivity

x ( x + x)

=
complement

neutral _ element

x

x+x

=
neutral _ element

( x + x) *1

=
complement

( x + x )( x + x ) = xx + xx

=
complement , previouse _ proof

x+x = x x+0 =

.2
x

neutral _ element

x +1 x *0 =
neutral _ element

=
neutral _ element

1*( x + 1) =

=
complement

( x + x )( x + 1) =
distributivity

=
distributivity

x +1 = 1 x + x *1 = x + x =

.3
1

complement

0 + ( x *0)

complement

( x * x ) + ( x *0)

x *( x + 0)

neutral _ element

x *0 = 0 = x*x =

.4
0

complement

x + xy x( x + y ) =
neutral _ element

=
neutral _ element

x *1 + xy =

=
ditributivity

x(1 + y )

=
commutativity

x + xy = x = x( y + 1) = x *1
y +1=1

.5

neutral _ element

x
.6

( x + 0)( x + y )

distributivity

x + (0* y )

=
commutativity

x( x + y ) = x x + ( y *0) = x + 0 =
x*0 = 0

neutral _ element

x
.7 .8

x( x + y ) = xy
x ( x + y ) = xx + xy = 0 + xy = xy

x + xy = x + y x + xy = ( x + x) *( x + y ) = 1*( x + y ) = x + y

:

:

: :

x1
1 2 3

f ( x0 , x1 ) = x0 x1 = F8

0 0

1 1

x0

x1

1

2

3

f ( x0 , x1 ) = x0 + x1 = F14

0 0

1 1
x0

x1

1

2

3

f ( x0 , x1 ) = x0 ⊕ x1 = F6

0 0

1 1
x0 f ( x0 , x1 ) = x0 + x1 = x0 ↓ x1 = F1

x1

1

2

3

0 0

1 1
x0

x1

f ( x0 , x1 ) = 0 = F0

1

2

3

0 0

1 1
x0

x1

f ( x0 , x1 ) = 1 = F15

1

2

3

0 0

1 1
x0

:"

"
f ( x0 , x1 ) = x0 x1 + x0 .1 x1

x1

x1

1

2

3

1

2

3 =

1

2

3

+
0 0 1 1
x0

0 0

1 1
x0

0 0

1 1
x0

f ( x0 , x1 ) = x0 x1 + x0 = x0 f ( x0 , x1 ) = x0 x1 ⊕ x0 .2

x1

x1

x1

1

2

3

1

2

3 =

1

2

3


0 0 1 1
x0

0 0

1 1
x0

0 0

1 1
x0

f ( x0 , x1 ) = x0 x1 ⊕ x0 = x0 x1

x

:

3-

100 101 111

110

000

y 010 011

001 z

x

f ( x, y, z ) = xyz

y

z

x

f ( x, y , z ) = y z

y

z x
f ( x, y , z ) = y

y

z f ( x, y, z ) = xy + x y = x ⊕ y x

y

z

:"
x
x⊕ y

"
x
z

3x


y

=
y y

z

z

z
x ⊕ y ⊕ z = xy ' z '+ xyz + x ' y ' z + x ' yz '

x
x⊕ y

x

z

x

*
y

=
y y

z

z

z

( x ⊕ y ) z = xy ' z + x ' yz

x
x⊕ y

x

z

x

+
y

=
y y

z

z

z